Media Credibility and Re-use Intention for Information Seeking in Crisis: A Case of Cross-Platform Media Complementary Effect in Covid-19 Pandemic in Vietnam - Nguyen, Doan Viet Phuong; Phung, Thanh-Binh (SAGE open, 2023)
The relationship among different media types is a long and exciting subject for researchers. It can not be denied that the rise of online media has contributed to the decline of traditional media consumption. Despite their conflict, traditional media can take full advantage of social media’s user base for their benefit. At one point in this relationship, the Covid-19 pandemic occurred as a massive event that changed the world beginning in 2020. In the new situation, people’s emotions, information seeking motivation, and intention change, ultimately affecting their choice of mediums to acquire information. The study found differences in people’s emotions, motivation, and medium’s re-use intention during the Covid-19 outbreaks and after they were controlled. Furthermore, the results illustrate that one medium’s re-use intention is affected by its credibility and other medium’s credibility and re-use intention. These impacts could signify the complementary effect in a multiplatform context.